The Influence of Experience Quality on Customer Loyalty Through Perceived Value and Satisfaction as Mediators - Laksono, Mohamad Iqbal Ajie; Sugiyanto (Universitas Mohammad Husni Thamrin, 2025)
In today's cafe industry, business owners face intense competition in attracting consumers to make purchases. Digital app-based food delivery services like ShopeeFood are growing rapidly in Indonesia, including in the Tangerang area. This intense competition demands that companies provide the best quality experience to maintain customer loyalty. Consumer behavior is essential because each customer has different characteristics and traits. This study aims to analyze the effect of experience quality on customer loyalty among ShopeeFood customers in Tangerang. The research method used was a quantitative approach with a survey design for 100 respondents selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) with the help of AMOS software. The results showed that experience quality has a positive and significant effect on customer loyalty, with a coefficient of determination of 43.6%, meaning this variable is able to explain almost half of the variation in customer loyalty. This finding indicates that improving the quality of the user experience, both in terms of ease of use of the application, on-time delivery, and interaction with drivers, can strengthen ShopeeFood customer loyalty. The recommendation for management is to continue optimizing the application's features, increasing supervision of driver partners, and maintaining consistent service quality in order to maintain and increase the customer base amidst the competition in the food delivery service industry.